SAT0474 Racial differences in ssc disease presentation: a european scleroderma trials and research group study. (12th June 2018) - Jaeger, V.K.; Siegert, E.; Hachulla, E.; Airò, P.; Valentini, G.; Matucci-Cerinic, M.; Distler, O.; Cozzi, F.; Allanore, Y.; Li, M.; Tikly, M.; Walker, U.A.; et al.
Abstract : Background: Genetic and environmental factors play a significant role in systemic sclerosis (SSc). African Americans are known for a higher SSc incidence, an earlier age of onset, and a greater frequency of interstitial lung disease and pulmonary hypertension (PH) compared to white patients. Data on blacks mostly stem from African Americans and studies on SSc in Asians are mostly from outside Asia and lack direct comparison with other racial groups. Objectives: We aimed to evaluate differences of SSc presentations between white, Asian and black patients. Methods: Characteristics of self-reported white, Asians or black SSc patients from the EUSTAR cohort were compared across racial groups; survival and multiple logistic regression analyses were used to adjust for age, sex, disease duration and antibody status. Results: 9162 white, 341 Asian and 181 black patients were included. Of the Asian patients 208 stem from within Asia and 133 from 34 centres outside Asia; of the black patients 65 stem from within Africa and 116 from 35 centres outside Africa. Asian and black patients were on average 10 years younger than white patients (p<0.001). Black patients developed the first non-Raynaud's phenomenon (RP) feature of SSc faster than Asian and white patients (all p<0.01; figure 1) also after adjustment (hazard ratio (HR)[blacks] 1.4, p<0.001; HR[Asians] 1.1, p=0.13 vs whites). Among ANA specificities, ACA predominated in white patients (whites: 40%, Asians: 16%, blacks: 10%; p<0.001) and Scl-70 in Asian patients (whites: 34%, Asians: 46%, blacks: 32%; p<0.001). The prevalence of diffuse skin involvement was similar in Asian (28%) and white patients (27%), but more common in black patients univariately (59%; p<0.001); however in multivariable analysis Asian patients were less likely to have diffuse SSc than white patients (OR 0.6, p=0.001) while black patients were more likely (OR2.9, p<0.001). The prevalence of PH (defined as PAPsys >40 mmHg as estimated by echocardiography) was similar in the three groups (whites: 13%, Asians: 17%, blacks: 14%; p=0.10); however multivariably, Asians were more likely to have PH (OR[Asians] 2.0, p<0.001, OR[black] 1.5, p=0.13 vs whites). Asians had a higher prevalence of an impaired diffusing capacity for carbon monoxide (DLCO;<80% of predicted; 84%) than black (72%) or white patients (69%, p<0.001) also in multivariable analysis (OR[Asians] 3.0, p<0.001; OR[blacks] 1.2, p=0.36 vs whites). Both, Asians (43%) and black patients (58%), had a higher prevalence of a reduced forced vital capacity (FVC;<80% of predicted) compared to white patients (23%, p<0.001) univariably and multivariably (OR[Asians] 2.4, p<0.001; OR[blacks] 4.0, p<0.001 vs whites). Patients who experienced their first non-RP feature of the disease before the onset of RP were included with a simultaneous onset. Conclusions: Several clinical and serological differences were evident between the three racial groups. Asians had high prevalences of Scl-70, PH and of a reduced FVC. Black patients in contrast had fast disease onset and a high prevalence of diffuse skin involvement. Disclosure of Interest: None declared